2022
DOI: 10.3324/haematol.2022.280847
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in adult acute myeloid leukemia patients: a long-term follow-up study from the European Hematology Association survey (EPICOVIDEHA)

Abstract: Patients with acute myeloid leukemia (AML) are at high risk of mortality from coronavirus disease 2019 (COVID-19). The optimal management of AML patients with COVID-19 has not been established. Our multicenter study included 388 adult AML patients with COVID-19 diagnosis between February 2020 and October 2021. The vast majority were receiving or had received AML treatment in the prior 3 months. COVID-19 was severe in 41.2% and critical in 21.1% of cases. The chemotherapeutic schedule was modified in 174 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
1
27
0
14
Order By: Relevance
“…Interestingly, Marchesi et al showed that a treatment delay was protective in a multivariate analysis for the clinical course of COVID-19, whereas therapy discontinuation was associated with worse outcomes. These results were also applicable to patients with newly diagnosed AML in whom a treatment delay was possible [ 31 ]. The Latin American study investigating 83 patients with AL reported therapy modifications in 49% of patients; the main modification was a delay of treatment, followed by a change in therapy scheme and a dose reduction (no data available about discontinuation).…”
Section: Impact Of Covid-19 On Al Treatmentmentioning
confidence: 96%
See 4 more Smart Citations
“…Interestingly, Marchesi et al showed that a treatment delay was protective in a multivariate analysis for the clinical course of COVID-19, whereas therapy discontinuation was associated with worse outcomes. These results were also applicable to patients with newly diagnosed AML in whom a treatment delay was possible [ 31 ]. The Latin American study investigating 83 patients with AL reported therapy modifications in 49% of patients; the main modification was a delay of treatment, followed by a change in therapy scheme and a dose reduction (no data available about discontinuation).…”
Section: Impact Of Covid-19 On Al Treatmentmentioning
confidence: 96%
“…Overall, across all COVID-19 waves, the SARS-CoV-2-associated mortality ranged from 20–52% in patients with AL [ 31 , 32 , 33 ]. However, no comprehensive data are yet available for the Omicron variant.…”
Section: Clinical Coursesmentioning
confidence: 99%
See 3 more Smart Citations